Effect of the inquiry-based nature of science argumentation instructional model in scientific literacy skills - Lestari, Diah Puji; Paidi, Paidi; Suwarjo, Suwarjo (Journal of Education and Learning (EduLearn), 2024)
The purpose of this study is to see how the inquiry-based nature of science (NOS) argumentation (IB-NOSA) instructional model affects scientific literacy skills. This research used a quasi-experimental method. The design of this research is a pretest-posttest control group design. This study describes the significance of the differences between participants who learn through IB-NOSA, guided inquiry, and discovery learning model. The subjects of this study were 288 students of grade VIII in the 2022/2023 academic year from three junior high schools in Sleman, Yogyakarta, Indonesia. Data analysis in this study used an analysis of variances (ANOVA) mixed design. The result showed that there was a difference between the pretest-posttest scores of scientific literacy skills in each group. There was a significant increase in the pretest-posttest scores of scientific literacy skills in each group. Effect size showed that the IB-NOSA in increased scientific literacy skills was 0.79; the guided inquiry was 0.76; and the discovery learning was 0.71. The IB-NOSA was the most effective in improving scientific literacy skills with a gain score of 0.49 (medium). So, it can be concluded that the IB-NOSA instructional model can be used as an alternative solution in improving scientific literacy skills.